2013
DOI: 10.1093/jscr/rjs038
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall abscess containing gallstones as a late complication to laparoscopic cholecystectomy performed 17 years earlier

Abstract: Laparoscopic cholecystectomy (LC) is the preferred surgical treatment for symptomatic gallstones. The laparoscopic procedure is superior to the open approach in many aspects. Intraperitoneal spillage of bile and gallstones is one of the most common accidental occurrences of LC. We present a case of a 53-year-old woman who developed two abscesses­—one intra-abdominally and one in the abdominal wall—17 years after an LC. Three gallstones were found during surgical excision of the abdominal wall abscess. Surgeons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…concluded that out of 129 cases of gallstone spillage, the conservative open approach had only two cases of this subsequent complication [ 2 ]. An array of various factors subsequently disposes to perforation such as the dissection of the gallbladder from the liver bed, the application of undue retraction of the gallbladder via forceps, as well as gallbladder extraction, which can also potentiate spillage [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…concluded that out of 129 cases of gallstone spillage, the conservative open approach had only two cases of this subsequent complication [ 2 ]. An array of various factors subsequently disposes to perforation such as the dissection of the gallbladder from the liver bed, the application of undue retraction of the gallbladder via forceps, as well as gallbladder extraction, which can also potentiate spillage [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated, the risk of perforation and spillage is high [ 1 ]. However, the subsequent development of actual complications secondary to a stone spillage is relatively rare, with an estimated incidence of 0.8%-8.5% [ 3 ]. This alludes to the understanding that certain risk factors influence the possibility of developing complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can happen many years after surgery, for example, in the case of a patient who presented with painful defecation due to an abscess in the pouch of Douglas, and was also found to have a small asymptomatic chronic anterior abdominal wall abscess 10. Gallstones have also been reported to lodge in the anterior abdominal wall during port removal after laparoscopic cholecystectomy—either at the level of the rectus sheath or internal oblique muscle—and to cause abscess formation up to 8 years after operation 11 12…”
Section: Discussionmentioning
confidence: 99%